2019
DOI: 10.1063/1.5120738
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctionalized silk fibroin nanofibers for directional and long neurite outgrowth

Abstract: Engineered scaffolds simultaneously exhibiting multiple cues are highly desirable for neural tissue regeneration. Silk fibroin is a promising natural protein material for nerve repair. However, the lack of specific bioactive cues significantly hinders its application. In this study, the electrospun silk fibroin nanofibers with both biochemical and topographical cues were prepared. The alignment of electrospun nanofibers was optimized by controlling the surface linear velocity of a rotating drum. The silk fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…SF fibers can be gathered in various collectors to make 2D and 3D highly arranged mats or weaves of different shapes. This method has the potential to fabricate highly arranged structures to guide cells and push them toward further proliferation, differentiation, and adhesion and to be used as conduits for axonal guidance and neuronal regeneration [44,99,100]. A main issue is the hardship of constructing structured 3D scaffolds to fill spatial defects in the nervous tissue [101].…”
Section: Fabrication Of Fiber-based Biomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…SF fibers can be gathered in various collectors to make 2D and 3D highly arranged mats or weaves of different shapes. This method has the potential to fabricate highly arranged structures to guide cells and push them toward further proliferation, differentiation, and adhesion and to be used as conduits for axonal guidance and neuronal regeneration [44,99,100]. A main issue is the hardship of constructing structured 3D scaffolds to fill spatial defects in the nervous tissue [101].…”
Section: Fabrication Of Fiber-based Biomaterialsmentioning
confidence: 99%
“…The cell attachment properties of SF biomaterials can be further improved by refining the residual negative charge of silk fibers [61]. Due to the lack of bioactive molecules in SF, the functionalization of this biomaterial with ECM proteins (such as fibronectin, laminin and collagen), ECM-adhesive peptides (such as the peptide sequences Ile-Lys-Val-Ala-Val; IKVAV and Arg-Gly-Asp; RGD) and growth factors (such as nerve growth factor and fibroblast growth factor [100]) have been applied in numerous studies.…”
Section: Improvement Of Cell Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…During in vitro culture, three-dimensional structures, such as grid patterns of extracellular matrix protein, increase NSC differentiation into neurons while decreasing differentiation into glial cells [ 14 ]. Recent stem cell studies demonstrated that NSCs respond strongly to the nanoscale topography of the matrix environment such as nanofiber and 3D-printed structures [ 15 , 16 , 17 , 18 , 19 ]. However, many previous studies have used limited types of nanoscopic geometries (e.g., nano-wires and nano-needles) as optimal artificial extracellular matrices (aECMs) [ 20 ], which limits control over differentiation into specific cell types.…”
Section: Introductionmentioning
confidence: 99%
“…[ 160 ] Additionally, naturally derived silk fibroin functionalized with laminin displayed enhanced and unidirectional neurite outgrowth. [ 161 ] Carbon nanotubes have been considered for guiding neuronal axon growth as well and demonstrate biocompatibility. [ 162 ] For NSC transplantation, a PEG‐4MAL based polymer that used affinity based binding of laminin to N‐terminal agrin (NtA) displayed higher bioactivity compared to alternative strategies to incorporate laminin into the synthetic polymer.…”
Section: Materials To Facilitate Cell Therapy For the Cnsmentioning
confidence: 99%